How to manage and survive during a global crisis : lessons for managers from the COVID-19 pandemic - Sharma, Piyush; Leung, Tak Yan (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Sharma and Leung explore the differences in the national and organisational responses to COVID-19 across various countries. The Covid-19 global pandemic is possibly the worst healthcare disaster ever and recent studies highlight several differences in the response to COVID-19. Some countries acted quickly with strict measures to successfully contain the initial spread of COVID and minimise the number of cases and deaths while others have not been as proactive and suffered more as a result. The book is organised under distinct themes based on the stages of Covid-19 pandemic, consisting of a. discovery and early response, b. global spread and reactions, c. early successes and failures, d. subsequent waves and new strains. It goes on to analyse the differences in national responses to draw important lessons for managers and governments and concludes with policy recommendations. A useful guide for students, managers, and the general public who are interested in learning about the COVID-19 experience and how such global crises could be managed more effectively in future"--
COVID-19 discovery and early response -- unveiling a global crisis -- COVID-19 global spread and reactions -- unity in diversity -- COVID-19 early successes and failures -- battling the unknown -- COVID-19 subsequent waves and new strains -- living with the enemy -- COVID-19 differences in national responses -- different strokes -- COVID-19 business response -- adaptation, resilience, and innovation -- COVID-19 important management lessons -- learning from failures -- Conclusion and recommendations.
Keywords: COVID-19 Pandemic, 2020- -- Government policy; COVID-19 Pandemic, 2020- -- Economic aspects; BUSINESS & ECONOMICS / Strategic Planning